2018
DOI: 10.1186/s40792-017-0413-0
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary adenocarcinoma possibly developed from the cut-end of small-sized adenocarcinoma in the lung periphery as recurrence 13 years after its wedge resection

Abstract: BackgroundIt is a big topic for general thoracic surgery whether still curability can be obtained by limited resection for peripheral small-sized nodules of non-small cell lung cancer (NSCLC) in the current era of frequent computed tomography (CT) use. Accumulation of information on problematic cases would be meaningful for surgeons to select better surgical procedures.Case presentationA 69-year-old man was pointed out an enlarged 2.1-cm solid nodule on the edge of staple line of the residual right upper lobe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
1
1
0
Order By: Relevance
“…However, in the overall comparison, there was no significant difference in the development time of margin granulomas and tumor recurrence. Consistent with other cases reported around the world ( 23 - 25 ), our study found a large variance in the time to recurrence in both types of masses. In other reports, some patients with relatively low-grade primary lung cancer who underwent wedge resection were found to have peri-margin recurrence after 13 years ( 25 ), and there were patients with metastatic lung cancer suspected of short-term margin recurrence that eventually proved to be granuloma ( 26 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, in the overall comparison, there was no significant difference in the development time of margin granulomas and tumor recurrence. Consistent with other cases reported around the world ( 23 - 25 ), our study found a large variance in the time to recurrence in both types of masses. In other reports, some patients with relatively low-grade primary lung cancer who underwent wedge resection were found to have peri-margin recurrence after 13 years ( 25 ), and there were patients with metastatic lung cancer suspected of short-term margin recurrence that eventually proved to be granuloma ( 26 ).…”
Section: Discussionsupporting
confidence: 92%
“…Normal mucosal epithelia, such as oral, colorectal, and bronchial mucosa secrete CEA, and smoking and aging also lead to elevated serum CEA ( 31 ). Some researchers have pointed out that DWIs has advantages in identifying recurrence in surgical margins and sutured granulomas after lung cancer surgery, but there are also limitations in misdiagnosis, tumor type, and the population examined ( 25 ). Even invasive biopsy cannot guarantee a complete diagnosis.…”
Section: Discussionmentioning
confidence: 99%